PERAN INOVASI DAN KEMITRAAN DALAM MENINGKATKAN KEUNGGULAN BERSAING UMKM BATIK SEMARANGAN - - Indarto; Teguh Ariefiantoro (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Batik Semarangan SMEs are required to increase their competitive advantage along with the revival ofbatik industry in various regions and the entry into force of the Economic Asean Community andglobal free market. This study   examined the role of innovation and partnership in improving thecompetitive advantage of Batik Semarangan SMEs. Data used in the study is primary data  which isobtained  through in-depth  interviews and focus group discussions. The population wereentrepreneurs and craftmen in Batik Semarangan SMEs. The result of descriptive analysis shows thatentrepreneurs and craftsmen Batik Semarangan growing well, judging from the number and productdevelopment. The entrepreneurs and craftsmen Batik Semarangan understand the importance ofimproving the competitive advantage of Batik Semarangan. Depth interview and observations‘s resultsdemonstrate that Batik Semarangan SMEs have to innovate although there are still many obstacles,but quite succses. The perpetrators in SMEs Batik Semarangan had to develop creativity, confidenceand empowerment in fostering innovation and partnerships. But this time Batik Semarangan SMEs isstill lacking in partnership, so marketing Batik Semarangan still limited. To examine the role of innovation and partnership on competitive advantage of SMEs Batik Semarangan used analysis Structural Equation Model (SEM). The results are ; empowerment have positif relationship to partnership ;   creatifity and adaptability have positive relationship to innovation; partnership haspositive relationship to innovation; innovation has positive relationship to competitive advantage. Unfortunately, trust has no effect to partnership;  partnership has no affect to competitive advantage.   Keywords: competitive advantage, innovation, partnerships, SMEs